Association between depression and hypertension in the Ibadan Study of Ageing. African (2020)
Introduction: The elderly population is growing all over the world with attendant increase in occurrence of comorbid conditions. Using data from a longitudinal study of community-dwelling elderly persons in Nigeria, we explored the prevalence and corelates of hypertension and depression as well as the factors associated with the comorbidity of these two conditions. Methods: The Ibadan Study of Ageing, a longitudinal community-based cohort study conducted between 2003 and 2009 on the profile and determinants of successful ageing. A multistage cluster random sampling was used to select a cohort of elderly participants from across eight contiguous Yoruba speaking states in Nigeria- Ekiti, Kogi, Kwara, Lagos, Ogun, Ondo, Osun, and Oyo. Participants (non-institutionalized elderly, aged 65 years or over) were assessed at 4 time points: baseline(2003/2004) and annually from 2007 (wave 1), 2008 (wave 2 and 2009 (wave 3). Data was collected in face-to-face interviews; depression was assessed using the World Mental Health initiative version of the Composite International Diagnostic Interview (CIDI), social engagement was assessed using an adapted World Health Organization Disability Assessment Schedule WHODAS) and functional disability using activities of daily living (ADL) and instrumental activities of daily living (IADL). Hypertension was defined according to the Joint National Committee-7(JNC7) recommendations as systolic blood pressure of 140 mmHg and above, diastolic blood pressure of 90mmHg. This current study is based on cross-sectional data from the wave 1(2007) assessment. Results: Of the 1597 participants, 58% were females and 42% were 70 years and older. The mean age was 74.2 years (SD ±7.8). Nine hundred and ninety-eight (62.5%) participants had hypertension while 177 (10.6%) met the criteria for major depression while comorbid depression and hypertension was present in 122 (7.1%). The comorbidity of hypertension and depression was significantly associated with gender (higher in women) (p=0.001), insomnia (p=0.001), lack of family participation (p=0.001), lack of community participation (p=0.002), and experiencing a negative life event in the past year (p=0.003). In a multivariate analysis, lack of participation in family activities was associated with an increased risk of co-morbidity between hypertension and depression (OR 4.51, p=0.000, CI 2.14-9.50). Conclusions: These findings suggest that the comorbidity of depression and hypertension could potentially be minimized by modifying social risk factors such as keeping the elderly involved in family and community life participation by promoting their involvement in recreational and volunteer activities as well as social gatherings.